Support for Small Businesses amid COVID-19 - Charles Goodhart; Dimitrios Tsomocos; Xuan Wang (Tinbergen Institute, 2021)
A sizeable proportion of enterprises, especially SMEs, assisted by the government, will fail to repay. Should a screening mechanism then be applied to deter those most likely to default from seeking such financial assistance? The answer depends on the relative weights attached to the competitive objectives of stabilisation and allocative efficiency. For this purpose, we develop a two-sector equilibrium model featuring oligopolistic small businesses with asymmetric private information and a screening contract. The sector adversely affected in a pandemic can apply for government loans to reopen later. A pro-allocation government sets a harsh default sanction to deter entrepreneurs with bad projects thereby improving productivity in the long run, at the cost of persistent unemployment, whereas a pro-stabilisation government sets a lenient default sanction. The optimal default sanction balances the trade-off between allocation and stabilisation. Finally, we solve for the optimal default sanction numerically and conduct comparative statics.
Keywords: H81; D82; E44; 330; COVID-19; Government Guarantees; optimal default sanction; unemployment; productivity; Adverse Selection; private information; screening